1984
DOI: 10.1079/bjn19840094
|View full text |Cite
|
Sign up to set email alerts
|

Methane formation in faunated and ciliate-free cattle and its relationship with rumen volatile fatty acid proportions

Abstract: 1. Twelve steers fitted with rumen cannulas were used in three separate experiments to investigate the effects of the presence or absence of rumen ciliate protozoa on methane production. The diet consisted of 850 g barley and 150 g protein supplement/kg, and was given in three feeds daily at a restricted level of 61 g/kg live eight^''^. Animals were defaunated initially by allowing ad lib. consumption of this diet and were then maintained ciliate-free by isolation or were faunated by inoculation with a mixed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
2
3

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(76 citation statements)
references
References 29 publications
10
59
2
3
Order By: Relevance
“…This was underlined by the fact that butyrate, a major product from sugar fermentation, was found to be positively correlated with methane production (r = 0.67; P < 0.001; n = 32). This relationship was also reported by Whitelaw et al (1984) and Pinares-Patiño et al (2003).…”
Section: Methanogenesissupporting
confidence: 70%
“…This was underlined by the fact that butyrate, a major product from sugar fermentation, was found to be positively correlated with methane production (r = 0.67; P < 0.001; n = 32). This relationship was also reported by Whitelaw et al (1984) and Pinares-Patiño et al (2003).…”
Section: Methanogenesissupporting
confidence: 70%
“…However, with the rising public and health authorities concerns about the use of chemical or antibiotic feed additives in animal production, the use of ionophores to mitigate CH 4 production might not be the best conceivable option. Defaunation Defaunation, which is the elimination of protozoa from the rumen by dietary or chemical agents, has been shown to reduce ruminal CH 4 production by about 20 to 50% depending on the diet composition (Whitelaw et al 1984;Itabashi et al 1994;Van Nevel and Demeyer 1996). Whitelaw et al (1984) observed that faunated cattle fed barley diets at restricted levels lost about 12% of GEI as CH 4 compared to 6-8% of GEI in ciliate-free animals.…”
Section: Ionophoresmentioning
confidence: 99%
“…Defaunation Defaunation, which is the elimination of protozoa from the rumen by dietary or chemical agents, has been shown to reduce ruminal CH 4 production by about 20 to 50% depending on the diet composition (Whitelaw et al 1984;Itabashi et al 1994;Van Nevel and Demeyer 1996). Whitelaw et al (1984) observed that faunated cattle fed barley diets at restricted levels lost about 12% of GEI as CH 4 compared to 6-8% of GEI in ciliate-free animals. Protozoa in the rumen are associated with a high proportion of H 2 production, and are closely associated with methanogens by providing a habitat for up to 20% of rumen methanogens (Stumm et al 1982;Newbold et al 1995a).…”
Section: Ionophoresmentioning
confidence: 99%
“…Higher feeding levels and/or grinding concentrate diets lowers protozoal count through acidification and increased tonicity associated with intensive fermentation, reduced salivation and lower k, values, although other factors may be involved (Lyle et al, 1981). Many animals on highconcentrate feeds are defaunated (Johnson, 1976) and high concentrate feeding is in fact an efficient defaunation procedure (Whitelaw et al, 1984a (Coleman, 1979).…”
Section: The Presence Of Protozoamentioning
confidence: 99%